Putative Connections Between Nitrate Reductase S-Nitrosylation and NO Synthesis Under Pathogen Attacks and Abiotic Stresses - Fu, Yu-Fan; Zhang, Zhong-Wei; Yuan, Shu (Frontiers in Plant Science, 2018)
Nitrate reductase (NR) is the key enzyme for nitrogen assimilation in plant cells and also works as an important enzymatic source of nitric oxide (NO), which then regulates plant growth and resistance to biotic and abiotic stresses. However, how NR activities are finely tuned to modulate these biological processes remain largely unknown. Here we present a SWISSPROT 3D analysis of different NR from plant sources indicating the possible sites of S-nitrosylation, and show some evidence of immunoblottings to S-nitrosated (SNO-) proteins. We also found that S-nitrosylation status of NR is negatively correlated with the enzyme activity. The production of NO via NR in vitro represents only 1% of its nitrate reduction activity, possibly due to NO generated through NR reaction may deactivate the enzyme by this S-nitrosylation-mediated negative-feedback regulation. NR-mediated NO generation also plays a key role in protecting plants from abiotic stresses through activating antioxidant enzymes and increasing antioxidants. Putative connections between NR S-nitrosylation and NO biosynthesis under pathogen attacks and abiotic stresses are discussed in this Perspective.